2022
DOI: 10.1101/2022.03.29.486257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolution of glycogen and glycogen-degrading activities reveals correlates of Lactobacillus crispatus dominance in a cohort of young African women

Abstract: Background: A healthy vaginal microbiome is dominated by Lactobacillus species that produce lactic acid, lowering vaginal pH and limiting colonization by pathogens. Lactobacillus dominance (LD) is established during puberty, but many women, especially those of Black race, lose LD during their reproductive years. Glycogen is thought to be a key host nutrient that supports vaginal lactobacilli and their fermentative lactic acid production, but mechanisms of glycogen utilization by Lactobacillus species are incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 97 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…However, given the positive relationship between amylopullulanase activity and smaller maltodextrins in the study by Lithgow et al [31], we think further studies should include analyses of metatranscriptomes and carbohydrate concentration, to clarify whether the observed in vitro pulA regulation, depending on carbohydrate availability in L. crispatus, corresponds to its in vivo regulation. Based on the prevalence of these carbon sources in vaginal metabolomics studies, as well as human amylase, we expect that L. crispatus in the vaginal environment preferentially relies on glycogen cleavage by other bacteria or host amylase and will only express amylopullulanase when other carbon sources are depleted.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, given the positive relationship between amylopullulanase activity and smaller maltodextrins in the study by Lithgow et al [31], we think further studies should include analyses of metatranscriptomes and carbohydrate concentration, to clarify whether the observed in vitro pulA regulation, depending on carbohydrate availability in L. crispatus, corresponds to its in vivo regulation. Based on the prevalence of these carbon sources in vaginal metabolomics studies, as well as human amylase, we expect that L. crispatus in the vaginal environment preferentially relies on glycogen cleavage by other bacteria or host amylase and will only express amylopullulanase when other carbon sources are depleted.…”
Section: Discussionmentioning
confidence: 87%
“…In most environments, L. crispatus maintains an intact amylopullulanase gene, even though disruption of the pulA gene occurs at relatively high frequencies. A recent metagenomics study and targeted PCR by Lithgow et al revealed that 36% of L. crispatus-dominated metagenomes from their African cohort lacked a functional L. crispatus pulA gene, and reported a threefold higher frequency of gene loss than that seen in metagenomes from European and North American women [31]. However, this is not reflected by the prevalence of disrupted pulA genes among the known ethnic groups in the metagenome data set of 1507 vaginal samples we have analyzed (Appendix A Table A1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore (Haddad et al, 2021) showed that the prevalence of vaginal candidiasis was higher in women who used contraceptives (84.1%) than in women who had not used contraceptives (15.9%), and there is a significant difference between the two groups. Previously, it was thought that oestrogen and progesterone hormones could manifest in contraceptives and increase vaginal glycogen, exposing it to lactobacilli activity (Lithgow et al, 2022). The pH of the vagina decreases as a result of the lactobacilli's function in the conversion of glycogen to lactic acid, which also inhibits the activities of the bacterial biota and promotes the growth of Candida species (Abdullah and Mohammed, 2020, Jasim, 2020).…”
Section: -Results and Discussionmentioning
confidence: 99%